Cash Flow Statements and Its Impact On Firms Valur - Dunakhir, Samirah (Universitas Negeri Makassar, 2023)
The research tries to explain the Cash Flow Statements and its impact on Manufacturing Firm Value Listed on the Indonesian Stock Exchange. The population in this study are all manufacturing companies in the sub-sector of various industries and consumer goods industries listed on the Indonesia Stock Exchange. The sampling method in this research is purposive sampling resulting a sample size of 120 in a period of 3 years 2018 to 2020. The data collection technique uses documentation techniques. Descriptive statistical analysis data, simple linear regression analysis, coefficient of determination test and t test are the method for data analyzing. The analysis results shows that there are significant effect of operating cash flow statements and investment cash flow statements on firm value, but there is no effect of the statements of cash flows funding on firm value. Based on the results of research on operating cash flow reports and investment cash flow reports of manufacturing companies listed on the Indonesia Stock Exchange for the 2018 - 2020 period, the firms’ value using Tobins'Q is getting better every year. However, the funding cash flow reports shows that the firms’ value is getting worse every year.